Two Suspicious Interviews of Neruda (Palimpsesto, 2019)
This article offers evidence on the manipulation experienced by two interviews of Neruda that appeared on El Mercurioa few days after his death. The discovery and recovery of the original interviews published by two international sources, and on El Mercurioone of them, allowed a comparison between the two versions. The September 1973 versions, appeared only a few weeks after the civic-military coup, deleted all the passages in which the poet talks about his political engagement and about the democratic identity of Salvador Allende’s government. The recovery of the original versions allowed the recovery of a fragment of the Chilean social memory hidden by El Mercurio in no giving information about the sources in which the interviews appeared.
Keywords: Pablo Neruda; El Mercurio; press censorship; social memory; coup d’etat